Factors associated with the quality of life and persistent dyspnea severity in COVID-19 survivors: A cross-sectional study among healthcare workers - Sinaga, Joshua P.; Sinaga, Bintang YM.; Siagian, Parluhutan; Eyanoer, Putri C.; Unata , Iduh M. (Narra Sains Indonesia, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has a significant impact on global health. The alterations in quality of life (QoL) and the persistent symptom of dyspnea have been the healthcare workers’ challenges during and after the pandemic. The aim of this study was to assess factors associated with the QoL and persistent dyspnea experienced by COVID-19 survivors, particularly among healthcare workers. A cross-sectional study was conducted among healthcare workers at H. Adam Malik Hospital, Medan, Indonesia, using direct interviews to collect the data. The EuroQol 5-dimensional 5-level (EQ-5D-5L) and the self-assessment EuroQol-visual analog scale (EQ-VAS) were used to assess the QoL of the healthcare workers; and persistent dyspnea was evaluated using the modified Medical Research Council (mMRC) scale. Possible risk factors such as demographic characteristics, clinical characteristics (comorbidities, history of hospitalization, oxygen usage, history of COVID-19 vaccination, the severity of previous COVID-19, existence of post-COVID syndrome) and the symptoms of the post-COVID syndrome were collected. Chi-squared test or Fisher’s exact test were used to identify the risk factors associated with the QoL and persistent dyspnea. A total of 100 healthcare workers were included in the study and 2% of healthcare workers experienced pain/discomfortand 4% experienced anxiety/depression. The average healthcare worker’s EQ-VAS score was 87.6±8.1. There was no significant association between studied demographics and clinical characteristics with QoL dimensions. However, post-COVID symptoms of activity limitation (p=0.004), sore throat (p=0.026), headache (p=0.012), myalgia (p=0.006), and arthralgia (p=0.001) were associated with pain/discomfort dimension of QoL. In addition, there was a significant association between activity limitation (p=0.012), headache (p=0.020), myalgia (p=0.015) and arthralgia (p=0.032) with anxiety/depression dimension of QoL. Our data suggested that the presence of post-COVID syndrome (p=0.006) and the presence of post-COVID syndrome symptoms of cough (p=0.021) and fatigue (p=0.015) were associated with the persistent dyspnea. In conclusion, this study suggests that the presence of post-COVID syndrome and its symptoms are associated with low quality of health-related QoL and persistent dyspnea. Therefore, cautions are needed for such patients to prevent low QoL in the future.